The cultural production of the educated person : critical ethnographies of schooling and local practice - Levinson, Bradley A., 1963-; Foley, Douglas E.; Holland, Dorothy C. (SUNY series, power, social identity, and education., 1996)
"Eleven historical-ethnographic case studies examine the social and cultural projects of modern schools, and the contestations, dramatic and not, that emerge in and around and against them. These case studies, ranging from Taiwan to South Texas, build upon an original joining of anthropology, critical education theory, and cultural studies. The studies advance the concept of cultural production as a way of understanding the dynamics of power and identity formation underlying different forms of "education." Using the concept of the "educated person" as a culture-specific construct, the authors examine conflicts and points of convergence between cultural practices and knowledges that are produced in and out of schools"--Jacket.